2013
DOI: 10.1177/1753193413511946
|View full text |Cite
|
Sign up to set email alerts
|

Pyrocarbon metacarpophalangeal joint replacement in primary osteoarthritis

Abstract: The purpose of this retrospective cohort study was to evaluate the outcomes of 18 primary pyrocarbon metacarpophalangeal joint replacements in 10 patients, performed for primary osteoarthritis. The mean age at operation was 66 years and mean follow-up was 58.6 months. The arc of motion improved from a mean of 30° to 40° and the mean QuickDASH score improved from 35 to 17. All except one patient were satisfied with their outcomes. Radiographically, there has been no evidence of dislocation or overt loosening, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
3
14
2
Order By: Relevance
“…When collateral ligament reconstruction is possible, either to an allograft or to native bone, unconstrained prosthesis including the pyrocarbon arthroplasty or surface replacement arthroplasty (SRA) is a viable option. 7,10,16,18,[20][21][22][23][24][25] This is an important consideration in younger patients given the high rate of fracture with silicone implants. 6,20 In our report, the patient initially had a satisfactory result after reconstruction with a fresh-frozen osteoarticular metacarpal head allograft.…”
Section: Discussionmentioning
confidence: 99%
“…When collateral ligament reconstruction is possible, either to an allograft or to native bone, unconstrained prosthesis including the pyrocarbon arthroplasty or surface replacement arthroplasty (SRA) is a viable option. 7,10,16,18,[20][21][22][23][24][25] This is an important consideration in younger patients given the high rate of fracture with silicone implants. 6,20 In our report, the patient initially had a satisfactory result after reconstruction with a fresh-frozen osteoarticular metacarpal head allograft.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, hard-bearing implants have been developed and used with good results in osteoarthritis ( Simpson-White et al, 2014), but are often too unstable in joints destroyed by inflammatory arthritis. There is still a need for soft (silicone) implants.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Reissner et al found that range of motion decreased from 36° pre-operatively to 29° at 10-year follow-up for pyrocarbon arthroplasty of the PIP joint (50). Conversely, Simpson-White et al found a 10° improvement in range of motion (30° pre-operatively to 40° post-operatively) at a mean follow-up of 58.6 months after arthroplasty of the MCP joint (51). Studies on pyrocarbon implant arthroplasty have also shown statistical improvements in grip and pinch strength (42, 47) as well as occupational performance (52).…”
Section: The Current Status Of Small Joint Arthroplastymentioning
confidence: 99%